The Effect of Workplace Facilities, Workload Management, and Job Flexibility on Employee Job Satisfaction in Insurance Companies in Indonesia - Subroto, Setyowati; Endrawati, Titin; Nawiyah, Nawiyah (West Science Interdisciplinary Studies, 2024)
This study investigates the effect of workplace facilities, workload management, and job flexibility on employee job satisfaction in insurance companies in Indonesia. A quantitative research approach was employed, involving 75 respondents from various insurance firms. Data were collected using a structured questionnaire based on a 5-point Likert scale and analyzed using SPSS version 26. Pearson correlation and multiple regression analysis were used to assess the relationships between the variables. The results show that all three independent variables—workplace facilities, workload management, and job flexibility—have a significant positive effect on employee job satisfaction. Among them, workplace facilities had the strongest influence, followed by job flexibility and workload management. The model explained 60.3% of the variance in job satisfaction, highlighting the critical role these factors play in enhancing employee morale and retention. The findings provide practical insights for insurance companies to improve job satisfaction by focusing on creating supportive work environments, managing workloads effectively, and offering flexible work arrangements.